Psychosocial and physiological health outcomes of outdoor green exercise versus indoor exercise in knee osteoarthritis patients coexisting with type 2 diabetes mellitus: a randomized controlled trial - Jin, Yilin; Geng, Xiang; Wang, Qiaojie; Xue, Feng; Lu, Shengdi; Huang, Lihua (Frontiers in Endocrinology, 2025)
BackgroundBoth physical activity and nature exposure are associated with several health benefits for both knee osteoarthritis (KOA) and type 2 diabetes mellitus (T2DM). However, the health outcomes when being physically active in nature, called green exercise (GE), are less clear. The purpose of this study is to evaluate the psychosocial and physiological outcomes for green exercise in KOA patients coexisting with T2DM compared to indoor exercise.MethodA prospective, randomized, open-label, parallel, multi-center clinical trial conducted at two hospitals in Shanghai that included 82 patients T2DM and KOA. Enrollment occurred between January 2020 and March 2022, and follow-up was completed October 2022. Participants were randomized to outdoor green cycling (OGC) group and indoor stationary cycling (ISC) group. Psychosocial and physiological health outcomes were evaluated through questionnaires comprising standard international measures of self-esteem (Rosenberg Self-esteem Scale [RSE]), perceived stress (Perceived Stress Scale [PSS]), mood (Profile of Mood States [POMS]) and nature relatedness (Nature Relatedness Scale – short-form version). Participants’ enjoyment of exercise and intention for a future exercise behavior was measured in a questionnaire using a 100mm visual analogue scale as a continuum from 0 – ‘not at all’ to 100 – ‘very much’.ResultsAmong 82 patients, 74 (90.2%) completed the trial. By 24 weeks, the OGC group showed a greater reduction in perceived stress (3.7 vs. 2.8, P = 0.007), and total mood disturbance (POMS) scores decreased more in the OGC group (-7.2 vs. -6.1, P = 0.030). Tension and depression subscales also showed greater reductions in the OGC group (P < 0.001 for both), along with higher improvements in vigor (10.2 vs. 8.1, P < 0.001). Enjoyment of exercise was slightly higher in the OGC group, though this difference did not reach statistical significance (P = 0.061), and their intention to continue exercising was also significantly stronger (P = 0.021). Participants in OGC group achieved significant decrease of HbA1c than participants in ISC group.ConclusionGreen exercise offers an accessible provision for improving short-term psychological wellbeing than indoor exercises.Clinical Trial Registrationhttps://www.chictr.org.cn/, identifier ChiCTR2100042872.